Specific classification and new therapeutic targets for neuroendocrine prostate cancer: A patient-based, diagnostic study - Wang, YouZhi; Wu, Ning; Wang, KeKe; Liao, YiHao; Guo, JiaNing; Zhong, BoQiang; Guo, Tao; Liang, JiaMing; Jiang, Ning (Frontiers in Genetics, 2022)
Objective Neuroendocrine prostate cancer (NEPC) is an aggressive variant of prostate cancer (PC) that may arise de novo or in patients previously treated with hormonal therapies for prostate adenocarcinoma as a mechanism of resistance. In our investigation, there appeared to be a strong correlation between neuroendocrine differentiation prostate cancer (NEDPC) and NEPC. The objectives of this study included exploring whether NEDPC is an intermediate stage in the progression of high-risk prostate cancer (HRPC) to NEPC and identifying risk factors and new targets associated with survival in the treatment of NEPC. Methods The selected prostate cancer patients were progressed to high-risk and characterized by neuroendocrine. We collected the clinical data and characteristics of patients with three types of cancer: the incidence of metastasis, site and time of metastasis, recurrence rate, related treatment methods, etc. The similarity and differences of the three groups were compared through experiment and database. Results By analyzing the clinical data and immunohistochemical results, we found that there seems to be a clinical feature of neuroendocrine differentiation (NED) status in between when patients progress from PC to NEPC. Finding novel treatment targets would therefore be beneficial by taking into account NEDPC as the stage of PC progression prior to NEPC. The metastasis-free survival curve and the immunohistochemical results are informing us that NEDPC can be a pre-state for diagnosing NEPC. Conclusions NEPC is a late PC symptom that is frequently disregarded and has a bad prognosis. Finding novel treatment targets would therefore be beneficial by taking into account NEDPC as the stage of PC progression prior to NEPC.